Diagnostic Significance of Ganglion Cells and Eosinophils in Appendicitis: An Adjunct to Histopathological Diagnosis - Susmitha, S; Bommanahalli, Basavaraj P (Annals of Pathology and Laboratory Medicine, 2019)
Background: Appendicectomy is most commonly performed intra-abdominal surgery. The exact etiopathogenesis of appendicitis is not exactly understood. Though eosinophils and ganglion cells are been observed routinely in appendix by many pathologists, little is being highlighted in literature in this regard. Present study was done to access the significance of mean cell count and topography of ganglion cells and eosinophils in association with histological type of appendicitis. Methods: It’s a retrospective study which included 93 appendicectomy specimens, out of which 65 were included. Remaining 28 cases with gangrenous change, perforation and neoplastic lesions were excluded. Mean cell count of eosinophils and ganglion cells was calculated. Topographical distribution and mean cell count of eosinophils and ganglion cells were correlated with histopathological type of appendicitis. The significance of association was calculated by chi-square test. Result: The mean eosinophil count was significantly higher in acute appendicitis compared to recurrent appendicitis with a p-value of <0.001. The ganglion cells were found to be more in acute appendicitis than recurrent appendicitis and was statistically significant (p=0.007). Topographic distribution of ganglion cells was predominantly noted within the circular layer only and between longitudinal and circular muscle layer along with circular layer of the muscularis propria in both acute and recurrent appendicitis. Conclusion: Mean count of eosinophils and ganglion cells were significantly increased in acute appendicitis. Hence, it may be considered as additional diagnostic criteria for acute appendicitis. Atypical localization of ganglion cells in circular layer was noted in both acute and recurrent appendicitis.